Analysis of the Generation State of Fine Precipitates in Steel - Ishida, Tomoharu; Yamada, Katsumi; Yamauchi, Katsuhisa (ISIJ International, 2022)
Fine precipitates in steel have various effects on the properties of steel products. Therefore, it is important to investigate the state of existence of precipitates in steel in order to consider their effect on the material. In this study, the size and shape of Nb and V precipitates were observed by electron microscopy and the amount of precipitates was evaluated by electrolytic extraction analysis in martensitic stainless steels which has excellent heat resistance. For steels with a certain chemical composition, stable chromium nitride (Cr2N) formation was observed when only Nb was added, whereas combined addition of Nb and V suppressed the formation of Cr2N and produced extremely fine precipitates in the steel (in lath martensite). The fine precipitates could be observed in thin film samples by using a high-resolution transmission electron microscope (TEM). In order to evaluate the state of formation of the fine precipitates in the steel quantitatively, the difference in the precipitation behaviors between the two materials was investigated by the size-classified quantitative analysis method. This method is considered to be a useful analytical technique in the development and design of high performance steels using fine nitrides and carbides with sizes of the several nm order.